2021
DOI: 10.3390/nu13030985
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Caloric Restriction Attenuates β-Amyloid Neuropathology and Is Accompanied by Autophagy in APPswe/PS1delta9 Mice

Abstract: Caloric restriction (CR) slows the aging process, extends lifespan, and exerts neuroprotective effects. It is widely accepted that CR attenuates β-amyloid (Aβ) neuropathology in models of Alzheimer’s disease (AD) by so-far unknown mechanisms. One promising process induced by CR is autophagy, which is known to degrade aggregated proteins such as amyloids. In addition, autophagy positively regulates glucose uptake and may improve cerebral hypometabolism—a hallmark of AD—and, consequently, neural activity. To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…A decrease in NAA levels is usually described in pathological conditions in clinical [27,28,33,34] and preclinical studies [35–37]. Our results in the EtOH group may therefore appear discordant with, on the one hand, a decrease in GABA/glutamate, which seems to reflect an impairment, and on the other, an increase in NAA, which could reflect an improvement in neuronal integrity [38]. However, this could reflect a repair process.…”
Section: Discussionsupporting
confidence: 48%
“…A decrease in NAA levels is usually described in pathological conditions in clinical [27,28,33,34] and preclinical studies [35–37]. Our results in the EtOH group may therefore appear discordant with, on the one hand, a decrease in GABA/glutamate, which seems to reflect an impairment, and on the other, an increase in NAA, which could reflect an improvement in neuronal integrity [38]. However, this could reflect a repair process.…”
Section: Discussionsupporting
confidence: 48%
“…To the best of our knowledge, the spine density of elderly people with insufficient protein intake has not been investigated thus far, but analogous to this result, there is a possibility that spine density in the brain has decreased in these populations as well. When discussing relationships between food intake and the brain, there are recent reports indicating that caloric restriction (CR) has positive effects on longevity and neurodegenerative diseases in animal studies (32)(33)(34). Müller et al (34) indicated that CR attenuated  amyloid deposition and increased autophagy in an AD model.…”
Section: Discussionmentioning
confidence: 99%
“…When discussing relationships between food intake and the brain, there are recent reports indicating that caloric restriction (CR) has positive effects on longevity and neurodegenerative diseases in animal studies (32)(33)(34). Müller et al (34) indicated that CR attenuated  amyloid deposition and increased autophagy in an AD model. In our experiments, caloric intake did not differ much in any group, and our data showed that autophagy in rTg4510 mice was not affected under either food condition (fig.…”
Section: Discussionmentioning
confidence: 99%
“…A CR dietary regimen prevented Aβ peptide production and plaque deposition in multiple models of AD, leading to the reduction of neuronal loss in the hippocampus and the improvement of cognitive deficits [ 332 , 333 , 334 , 335 , 336 , 337 , 338 ]. Mechanisms triggered by CR include promotion of anti-amyloidogenic alpha-secretase activity and induction of the NAD + -dependent Sirt1 deacetylase and autophagy [ 332 , 334 , 339 , 340 ]. Both animal and human studies have shown that CR benefits general health, improves memory and cognition, and slows down the aging process.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%